Case Study as teaching strategy in training of students in Library Science - González Pérez, Esteban (e-Ciencias de la Información, 2015)
This paper proposes a theoretical basis and some guidelines for implementing the study of cases in the academic training of students of the majors offered by the School of Library and Information Science at the University of Costa Rica. This teaching strategy can be successful in situations in wich the application of theory and practice to study different subjects is required, because these subjects are a product of real situations or problems from work activity and encourage the search for solutions, creativity, negotiation, teamwork, leadership, among many other attitudes and skills. This work starts from the perspective of constructivist that promotes meaningful learning and allows teachers and students to assume different roles in the construction of new knowledge.